Occupational exposure to endocrine-disrupting chemicals and the risk of uveal melanoma - Thomas Behrens; Elsebeth Lynge; Ian Cree; Jean-Michel Lutz; Mikael Eriksson; Pascal Guénel; Franco Merletti; Maria Morales-; Noemia Afonso; Aivars Stengrevics; Andreas Stang; Joëlle Févotte; et al. (Nordic Association of Occupational Safety and Health (NOROSH), 2012)
OBJECTIVES: We investigated the association between occupational exposure to endocrine-disrupting chemicals (EDC) and the risk of uveal melanoma using international data of a case-control study from nine European countries. METHODS: After exclusion of proxy interviews, 280 cases and 3084 control subjects were included in the final analysis. Information on possible exposure to EDC was derived from 27 job-specific questionnaires (JSQ), which solicited detailed questions on occupational tasks. Relative risk estimates were based on the JSQ and potential exposure to a group of endocrine-disrupting agents. We constructed several exposure scores, taking into account intensity of exposure, use of personal protective equipment, and exposure duration. We calculated unconditional logistic regression analyses, adjusting for country, age, sex, eye color and a history of ocular damage due to intense ultraviolet (UV) exposure. RESULTS: The overall exposure prevalence to EDC was low reaching a maximum of 11% for heavy metals with endocrine-disrupting properties. Although working in some industries was associated with increased melanoma risk [such as dry cleaning: odds ratio (OR) 6.15, 95% confidence interval (95% CI) 2.0-18.96 and working in the glass manufacturing industry: OR 3.49, 95% CI 1.10-11.10], agent-specific risks were not elevated. The strongest possible risk increase was observed for organic solvents with endocrine-disrupting properties (OR 1.31, 95% CI 0.78-2.21). Calculation of exposure scores did not indicate consistently elevated results with higher score values. Sensitivity analyses did not alter these results. CONCLUSION: Occupational exposure to EDC was not associated with an increased risk for uveal melanoma.